A longitudinal study: Microbiological evaluation of two halal beef slaughterhouses in the United States. (July 2021) - Al-Mahmood, Omar; Bridges, William C.; Jiang, Xiuping; Fraser, Angela M.
Abstract: Most evidence about the hygienic condition of halal food is derived from studies conducted in Muslim-majority countries, not western countries. Because context of practice is different in Muslim-majority countries, it is difficult to apply these findings to western countries, such as the United States. We aimed to determine the hygienic condition of beef carcasses and environmental surfaces in two U.S. halal beef slaughterhouses over a 12-month period. Each month between November 2016 and October 2017 samples were collected [N = 432 carcass samples (pre- and post-evisceration)] and 59 surface samples (slaughter hall floor, brisket saw, and offal table). All carcass and surface samples were analyzed for detectable levels of four indicator organisms – aerobic plate count (APC), Enterobacteriaceae count (EC), total coliform count (TCC), and generic Escherichia coli (ECC). All indicator organisms (APC, ECC, TCC, and EC) in samples collected from both plants were within acceptable limits based on USDA microbiological guidelines of beef carcasses. Significant differences ( P < 0.001) in the detectable levels of indicator organisms between pre- and post-evisceration were shown in plant B but not plant A. A significant difference ( P < 0.01) in detectable levels of all indicator organisms was shown between winter and summer. Levels were higher during the summer (June–September) in pre-evisceration samples at both plants compared to samples collected in the winter (December–February). These findings can be used to inform food safety interventions targeting halal beef slaughter operations in the United States. Highlights: Indicator counts in both plants were below acceptable limits. Indicator counts in both plants were higher in summer compared to winter. Indicator counts varied based on carcass sampling site.